2009
DOI: 10.1063/1.3272796
|View full text |Cite
|
Sign up to set email alerts
|

Automatic derivation and evaluation of vibrational coupled cluster theory equations

Abstract: A scheme for automatic derivation and evaluation of the expressions occurring in vibrational coupled cluster theory is introduced. The method is based on a Baker-Campbell-Hausdorff expansion of the similarity transformed Hamiltonian and is general both with respect to the excitation level in the parameter space and the mode coupling level in the Hamiltonian. In addition to deriving general expressions, intermediates that lower the computational scaling are automatically detected. The final equations are then e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 47 publications
1
129
0
Order By: Relevance
“…Although both VCI [n] and VCC[n] converge towards the FVCI when n is incremented to the full space, VCC[n] exhibits a faster convergence compared to VCI[n]. 13,14 Further recent improvements in the VCC methodology extending its range of applicability, include new implementations with well-defined polynomial computational scaling at all levels, 15 intermediate models inspired by perturbation theory, 16,17 and new VCC response theory based methods. 14,18,19 Recently, one of the authors 20 has proposed the use of variationally optimized coordinates for vibrational structure calculations in place of the conventional normal coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…Although both VCI [n] and VCC[n] converge towards the FVCI when n is incremented to the full space, VCC[n] exhibits a faster convergence compared to VCI[n]. 13,14 Further recent improvements in the VCC methodology extending its range of applicability, include new implementations with well-defined polynomial computational scaling at all levels, 15 intermediate models inspired by perturbation theory, 16,17 and new VCC response theory based methods. 14,18,19 Recently, one of the authors 20 has proposed the use of variationally optimized coordinates for vibrational structure calculations in place of the conventional normal coordinates.…”
Section: Introductionmentioning
confidence: 99%
“…(13). i m denotes the reference modal of mode m, u m the modal of mode m that is occupied in | µ m ⟩, and v m the modal occupied in |ν m ⟩.…”
Section: B Perturbative Measuresmentioning
confidence: 99%
“…This has been illustrated by automatic derivation and analysis. 13,14 Still, the polynomial scaling quickly leads to costly computations. For VCC, it has been shown that for large model systems that are actually decoupled, the computational cost can be reduced significantly by exploiting this decoupling in the parameterization.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29] The coupled cluster method has been established as one of the most accurate methods for the description of the many body systems. [30][31][32][33][34][35] In this method, the ground state of a many body system is obtained by the action of an exponential wave operator on an optimized a) Electronic mail: s.pal@ncl.res.in.…”
Section: Introductionmentioning
confidence: 99%